New approach for the assessment of train/track/foundation dynamics using in-situ measurements of high-speed train induced vibrations. Issue 116 (January 2019) - Mezeh, Reda; Mroueh, Hussein; Hosseingholian, Mohsen; Sadek, Marwan
Abstract: This paper presents an experimentally validated numerical model for the simulation of the complex dynamic response of the ballasted track foundation under the excitation of a moving high-speed train. It consists of an infinite Euler-Bernoulli beam that rests on continuous viscoelastic foundation. This study is carried out within the frame of the project: high-speed line "Bretagne" - "Pays de la Loire" (BPL) in which an instrumented straight track with classical ballasted formation is considered. A huge database of measurements is obtained, that's why a preliminary treatment of the field measurements (rail-foundation displacement histories) is performed in order to eliminate the unwanted high-frequency components (noise) from the raw data. Subsequently, the treated data is used to calibrate the dynamic impedances of the simplified foundation model using an iterative curve fitting procedure. In this work, an additional parameter is introduced to model the wheel load diffusion in the track structure. It is represented by the length of the loaded segment beneath the wheel in which the load distribution is inspired from the wheel-induced displacement field. Appropriate charts are given in the velocity range 162–342 km/h. The numerical experiments prove an important capacity of the model to achieve satisfactory results with significantly limited computational effort in view of the modest number of involved degrees of freedom. The use of relevant input parameters increases the efficiency in minimizing the error between measurements and predictions. The findings are very useful for researchers and practitioners working in railway track design. Highlights: The dynamic behavior of classical ballasted track is studied for wide range of train traveling velocities. The ballasted formation is represented by continuous viscoelastic foundation. Experimentally-validated dynamic impedances of the equivalent foundation are proposed for the prediction of track response. The wheel impact on the track structure is modeled by means of exponentially distributed load.